The structural characteristics of the wall of carotid arteries in older women and their prospective determinants in the population - S. K. Malyutina; Yu. Yu. Palekhina; A. N. Ryabikov; S. G. Shakhmatov; M. Bobak (Атеросклероз, 2014)
Purpose: To study the age gradient and prospective determinants of the structural characteristics of the arterial wall in the Novosibirsk population of older women (in the cross-sectional and prospective analysis).